Electromyographic validation of the muscles deltoid (anterior portion) and pectoralis major (clavicular portion) in military press exercises with middle grip - Bull, M. L. [UNESP]; Ferreira, M. I.; Vitti, M. (My University, 2011)
With the objective to know the electromyographic activity normal parameters of the deltoid (anterior portion) and pectoralis major (clavicular portion) muscles in the different modalities of military press exercises with middle grip, we analyzed 24 male volunteers using a two-channel electromyograph TECA TE 4, and Hewllet Packard surface electrodes. It was observed high inactivity levels for PMC in almost all the modalities and the concentration in the active cases, mainly, in the weak potential, while DA presented very high levels of much strong action potentials in all the modalities assessed.
Keywords: Electromyography; Exercises; Muscle deltoid; Muscle pectoralis major; Physical conditioning